Development of prognostic scenarios for sustainable development of a higher education institution: main approaches. (Journal of Educational Sciences, 2016)
Based on researches of sociologists, economists and mathematicians the authors of this article determined special aspects of mathematical forecasting of dynamic systems and specifics of drawing up prognostic scenarios for development of a higher education institution (“HEI”). Interrelations of main contemporary trends in the development of HEIs to ensure their sustainability were defined: expansion of academic freedoms, introduction of autonomy and strengthening of social responsibility. We want to note that the forecast is a probabilistic assessment of future results of education system, ways of its development, resources and organizational actions necessary for its sustainability. In the process of drawing up forecasts for development of education system, it is necessary to comply with methodical principles and the principles of social forecasting. Moreover, application of methods of mathematical modeling to social processes implies strict requirements to the methodology of such modeling. There are three established directions in it: linearly extrapolative methodology; the Forsythe methodology based on collective expert assessment; the methodology based on cyclic genetic laws of development. Equations on indicators characterizing the academic results of a HEI were generated. The above academic results are components of the sustainable development of a HEI and are necessary to develop a real system of forecasting sustainable development of a HEI under the conditions of its privatization.
Keywords: high school; University; academic freedom; sustainable development of the University